Narratives of speaking anxiety under evaluative pressure in students’ classroom presentations: A communication apprehension perspective by DeVito - Baharman, Baharman; Djumingin, Sulastriningsih; Suriadi, Suriadi; Safitri, Nur Anita Syamsi (Faculty of Languages, Arts, and Culture Universitas Negeri Yogyakarta, 2026)
Classroom presentations in higher education not only function as a means of developing students’ speaking skills but also frequently become evaluative situations that trigger speaking anxiety. This study focuses on students’ narratives of speaking anxiety under evaluative pressure in classroom presentations by employing DeVito’s concept of communication apprehension. This study aimed to explain how students narrate their experiences of speaking anxiety and identify the main categories that shape those experiences. This study employed a descriptive qualitative approach with a narrative analysis design. Data were collected through a Google Form containing open-ended questions distributed to all respondents and were then analyzed through the stages of data condensation, coding, categorization, data display, and conclusion drawing and verification. The findings show that students’ speaking anxiety is primarily shaped by fear of verbal/cognitive errors, fear of negative audience evaluation, performative/nonverbal symptoms, feelings of shame or lack of confidence, lack of experience and preparation, and previous negative experiences. The conclusion of this study confirms that communication apprehension in classroom presentations is not merely an individual feeling of nervousness but a communicative experience shaped by evaluative pressure and students’ meaning-making of errors, audience responses, and the social risks of speaking.